2017
DOI: 10.1590/0034-7167-2015-0169
|View full text |Cite
|
Sign up to set email alerts
|

Letramento funcional em saúde e conhecimento de doentes renais em tratamento pré-dialítico

Abstract: Objective: to analyze the functional health literacy (FHL), i.e., understanding and knowledge about chronic renal disease of 60 patients in pre-dialytic treatment. Method: this is a cross-sectional study. FHL was measured by B-TOFHLA; and the knowledge, by questionnaire. Pearson correlation and Chi-square tests were carried out as well as linear regression models. Results: all respondents presented inadequate FHL, and most showed insuffi cient knowledge about the disease and treatment. Low schooling was a pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
23

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 20 publications
1
28
1
23
Order By: Relevance
“…Os dados coletados apontam para um número maior de pacientes do sexo masculino, o que se apresenta de forma similar em estudos anteriores, fato este que pode possuir relação com aumento da violência urbana, uso de drogas lícitas ou ilícitas, menor procura e utilização dos serviços de saúde e serviços de prevenção e procura tardia do atendimento médico, situações mais comumente observadas em homens (4)(5) . Embora evidências científicas apontem para um predomínio de idosos portadores de doenças que levem à constituição de estomias (6) , a necessidade de atenção à prevenção de doenças e promoção da saúde destinada aos indivíduos das demais faixas etárias permanece.…”
Section: Discussionunclassified
“…Os dados coletados apontam para um número maior de pacientes do sexo masculino, o que se apresenta de forma similar em estudos anteriores, fato este que pode possuir relação com aumento da violência urbana, uso de drogas lícitas ou ilícitas, menor procura e utilização dos serviços de saúde e serviços de prevenção e procura tardia do atendimento médico, situações mais comumente observadas em homens (4)(5) . Embora evidências científicas apontem para um predomínio de idosos portadores de doenças que levem à constituição de estomias (6) , a necessidade de atenção à prevenção de doenças e promoção da saúde destinada aos indivíduos das demais faixas etárias permanece.…”
Section: Discussionunclassified
“…We observed that the studies conducted in Brazil have assessed the HL of individuals in specific populations, such as adults and seniors (1,(11)(12) , people with distinct health aggravations, such as diabetes (5,13) , cardiovascular diseases (14) and chronic kidney disease (15) , or in individuals in continuous use of medicines (16) , but only few studies assessed the HL of adults with hypertension (15) , in particular those who are treated in the Primary Health Care (PHC).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the Brazilian overview of functional health literacy, studies on this subject have only recently been published by national researchers more frequently (15)(16)(17)(18)(19)(20)(21) . In these articles, adequate functional health literacy may allow a prospective learning facilitator to play a role in the caring process of cardiac pacemaker patients (15) .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in patients with chronic kidney disease, it is urgent to improve functional literacy in the health of such patients. The use of a primer based on functional health literacy can help health professionals communicate better with such sick people, possibly by optimizing therapeutic outcomes (17,19) .…”
Section: Introductionmentioning
confidence: 99%